2018
DOI: 10.3389/fphys.2018.00775
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Representative Gut Microbiota Dysbiosis in Metformin-Treated Type 2 Diabetes Patients Using Genome-Scale Metabolic Modeling

Abstract: Dysbiosis in the gut microbiome composition may be promoted by therapeutic drugs such as metformin, the world’s most prescribed antidiabetic drug. Under metformin treatment, disturbances of the intestinal microbes lead to increased abundance of Escherichia spp., Akkermansia muciniphila, Subdoligranulum variabile and decreased abundance of Intestinibacter bartlettii. This alteration may potentially lead to adverse effects on the host metabolism, with the depletion of butyrate producer genus. However, an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 51 publications
(110 reference statements)
0
71
0
3
Order By: Relevance
“…This effect is consistent with the enrichment of short chain fatty acid (SCFA)-producing bacteria including Akkermansia, Bifidobacterium, Blautia, Butyrivibrio, Lactobacillus, Megasphaera, Prevotella or Shewanella species in metformintreated patients with T2DM, which results in increased SCFA in the colon, with potential metabolic benefits for the host 22,[187][188][189][190] . Interestingly, in silico analysis of the prevalent human gut bacterial metabolism using genome-scale metabolic models revealed important commensal and competing behavior following metformin treatment in the production of important SCFAs and their association with host cellular metabolism 191 .…”
Section: Modulation Of Gut Microbiotamentioning
confidence: 99%
“…This effect is consistent with the enrichment of short chain fatty acid (SCFA)-producing bacteria including Akkermansia, Bifidobacterium, Blautia, Butyrivibrio, Lactobacillus, Megasphaera, Prevotella or Shewanella species in metformintreated patients with T2DM, which results in increased SCFA in the colon, with potential metabolic benefits for the host 22,[187][188][189][190] . Interestingly, in silico analysis of the prevalent human gut bacterial metabolism using genome-scale metabolic models revealed important commensal and competing behavior following metformin treatment in the production of important SCFAs and their association with host cellular metabolism 191 .…”
Section: Modulation Of Gut Microbiotamentioning
confidence: 99%
“…Alterations in gut microbiota have been associated with dysglycaemia, including on people with prediabetes . Treatment with type 2 diabetes patients with metformin has been shown to alter the relative abundance of individual microbial species within the gut, particularly increasing the number of bacteria that produce short‐chain fatty acids or reduce the abundance of bacteria producing branched amino acids associated with insulin resistance . A recent randomized trial demonstrated altered gut microbiota during metformin treatment of antidiabetic drug‐naïve type 2 diabetes patients .…”
Section: Antihyperglycaemic Mechanismsmentioning
confidence: 99%
“…Bacterial species as well as metabolic pathways can have distinct patterns when they are examined at DNA (“standing”) level and RNA (“active”) levels 25, 26 . In defecated fecal samples, a collection of bacterial species including Ruminococcus , Subdoligranulum and Faecalibacterium are highly active in terms of transcription and potentially metabolism, and they belong to the increasingly well-appreciated group of butyrate producers, and butyrate is known to be both metabolically as well as immunologically crucial for the host, especially in the context of several metabolic as well as auto-immune disorders 28, 29, 30, 31 . Except the top pathway being adenosine ribonucleotides de novo biosynthesis that is related to ATP production and thus energy cycling in both DNA and RNA, metabolic pathways related to nutrients metabolism (for instance glucose metabolism) are highly active in transcriptome data, even though pathways related cellular structures (for instance, components of cell walls) are most abundant in DNAs, suggesting a heterogeneous regulation of transcription in pathways aimed at different parts of microbial physiological activities.…”
Section: Discussionmentioning
confidence: 99%